Recent theories of profit : a critical examination - Siddiqi, Muhammad Nejatullah; Aligarh Muslim University. Faculty of Social Sciences ([Bombay : Asia Publishing House, 1971)
This brief study reviews the profit theories of the last five decades. It fills the gap of the integration of the micro and macroeconomic attention theories to profit.
Includes bibliographical references.
uaa 24/01/2019
Loans.
Keywords: Profits; Profit theories